Relationship model among sport event image, destination image, and tourist satisfaction of Tour de Singkarak in West Sumatera - Ratni Prima Lita; Ma’ruf Ma’ruf (Journal of Economics, Business, and Accountancy Ventura, 2015)
Sport events Tour de Singkarak (TDS) can increase tourist arrivals to West Sumatera. At least at the time of execution, the majority of participants and team supporters (sports tourist) brings the families. Although there are claims about the arrival of tourists, it requires to see the impact of sports events TDS and comprehensive long-term basis to the West Sumatera image as a tourist destination (destination image) and its impact on tourist satisfaction. This study re-conceptualizes the interconnec-tedness among sport event image, tourist destination image, perception and the effect on tourists’ satisfaction. The investigation on this interconnection is expected to reveal empirically tested model. As an explanatory in nature, this study uses explanatory survey and cross sectional data. In total of 100 spectators of Tour de Singkarak in West Sumatera, they got involved in survey and they were taken by convenience sam-pling technique. Analysis of this data was done by using variance based structural equation modeling. It was found that sport event image and destination image signifi-cantly affect the satisfaction of spectators of Tour de Singkarak.